Pengaruh Model Project-Based Learning (Pjbl) Berbantuan Virtual Laboratory terhadap Kemampuan Pemecahan Masalah Siswa SMP pada Materi IPA - Amelia Fiska Fajar Cahyani (Fakultas Keguruan dan ilmu Pendidikan, 2026)
This study aims to determine the effect of the Project-Based Learning (PjBL) model assisted by a Virtual Laboratory on junior high school students' problem-solving skills in science learning. This research employed an experimental method with a pretest-posttest control group design. The population consisted of all eighth-grade students of SMP Negeri 1 Arjasa in the 2025/2026 academic year, with two classes selected as samples using purposive sampling, namely the experimental and control groups. The research instrument was an essay test designed to measure problem-solving skills based on four indicators. Data analysis was conducted using the Shapiro-Wilk normality test, Levene homogeneity test, Independent Sample T-test for hypothesis testing, and N-gain calculation to determine improvement. The results showed that there was a significant effect of the PjBL model assisted by a Virtual Laboratory on students’ problem-solving skills. The improvement in the experimental class was higher than in the control class. Therefore, the PjBL model assisted by a Virtual Laboratory is effective in improving students' problem-solving skills in science learning.
Approved by Teddy
Keywords: Project-Based Learning; Virtual Laboratory; problem-solving skills; science learning